RANCANG BANGUN ALAT PERONTOK LADA MODEL AKSIAL - TATANG HIDAYAT; RISFAHERI RISFAHERI; NANAN NURDJANNAH (Jurnal Penelitian Tanaman Industri, 2001)
Design of axialflow thresherfor pepperThe pepper threshing practice has been carried out using traditional method in which the pepper berries are usually trampled. This method is neither efficient nor higienic, and it also causes high losses of the berries. To overcome those problems, an experiment was carried out to make an axial flow thresher. The experiment was conducted at Research Institute for Spice and Medicinal Crops from April to December 1999. The experiment consisted of three steps, namely designing, constructing and testing. The objective of testing was to determine the optimum operation condition of the thresher. The testing was designed as a completely randomized complete design with three replications. The raw material for testing was pepper berries (Lampung Daun Lebar variety) of 8 - 9 month old. The result showed that the optimum condition for threshing process was 300 rpm cylinder rotation, with the spike separation process using 7.5° sieve angle. The performance of pepper thresher on that condition was : threshing eficiency 98.55%, spikes separation eficiency 89.22%, berries on spikes outlet 5.20% and berries damage 6.30%. The capacity of thresher was 260.56 kg raw material/hour. The operational cost was Rp 27.28/kg raw material, lower than that of the traditional threshing method (Rp 50/kg raw material).